Change of Function and Space of Puri in Bali: A Social History - Gde Djaja Bharuna S, A. A.; Salain, P. R.; Suartika, G. A. M.; Acwin Dwijendra, N. K. (International Journal of Engineering and Emerging Technology; Vol 3 No 1 (2018): January - June, 2018)
Puri is one of the traditional Balinese architecture, which is a palace. The form is a complex of buildings that function as the center of government and the residence of the king and his family. Like other palaces, puri in Bali has unique and distinctive features, making it interesting to study.As time passes, Balinese traditional architecture undergoes development and change, puri-puri in Bali are also not free from that, in line with the development of Balinese socioculture. Changes in the puri in Bali basically caused by two main factors, namely external factors, as well as internal factors. The research is aimed to intended to identify factors causing changes in the puri , both in terms of function and spatial. The study will be conducted with a social-historical approach , an approach in the field of architecture that has not been done. The proposition begins with a description of the socio-cultural background of the community and proceeds with a study of the physical changes that occur. The results of the study are expected to be used to anticipate and control more worrying changes in the future